SISTEM PENUNJANG KEPUTUSAN PEMILIHAN KETUA RT 10 DESA SUKAJAYA RW 15 DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Sulistiawan, Sulistiawan; Solihin, Gesit; Fitria, Farhana; Widyastuti, Reni (Penerbit Lafadz Jaya, 2024)
The selection of the Head of RT in Sukajaya Village RW 15 is a crucial process in the development of the local community. This research aims to evaluate the effectiveness of implementing the Decision Support System (DSS) based on the Simple Additive Weighting (SAW) method in the selection of the Head of RT. The focus of the research is on the role of DSS in improving the transparency, objectivity, and efficiency of the selection process, as well as its impact on community participation and community development. The research method involves direct observation, interviews, and literature review. The results show that the use of SAW in DSS can improve the objectivity and efficiency of the selection process of the Head of RT, and positively impact community participation in village development. This study contributes to the development of a more modern and transparent leadership selection system at the local level.